2017
DOI: 10.1080/24750573.2017.1367551
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and neglect in adult attention-deficit/hyperactivity disorder

Abstract: Objective: Although it has been suggested that attention-deficit/hyperactivity disorder (ADHD) is common in children who were abused and that ADHD can be a risk factor for abuse itself, there are very few studies which investigated whether adult ADHD is associated with childhood abuse and neglect. The aim of this study was to fill this gap in the literature. Method: Seventy adults with DSM-IV ADHD diagnosis and 70 healthy control subjects were included in the study. We used Adult ADHD Self Rating Scale (ASRS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Sanderud et al also found that emotional abuse was the second factor associated with ADHD symptoms in young adults (42). Semiz et al reported that emotional abuse and neglect are common (40). In our study, patients with ADHD differed in terms of emotional abuse, physical neglect and physical abuse scores.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Sanderud et al also found that emotional abuse was the second factor associated with ADHD symptoms in young adults (42). Semiz et al reported that emotional abuse and neglect are common (40). In our study, patients with ADHD differed in terms of emotional abuse, physical neglect and physical abuse scores.…”
Section: Discussionsupporting
confidence: 53%
“…When these results are compared with other studies conducted in children, it is seen that du Prel Carroll et al (2008) found a relationship between inattentive type ADHD and physical neglect, physical abuse and sexual abuse, and reported a relationship between hyperactive type ADHD and physical neglect (50). Semiz et al also found a relationship between hyperactivity/impulsivity scores and emotional neglect and abuse, and between inattention and emotional abuse in adults (40). Since emotional neglect and sexual abuse is a non-specific risk factor for any psychiatric disorder, this may be the reason for the lack of significant difference between ADHD subtypes (15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Bavilacqua et al [36], the cut-off scores for each subscale were for sexual abuse ≥8, physical abuse ≥8, emotional abuse ≥10, physical neglect ≥8, and emotional neglect ≥15. The internal consistency coefficient of the English version ranged from 0.84 to 0.89 for emotional abuse, 0.81 to 0.86 for physical abuse, 0.92 to 0.95 for sexual abuse, 0.85 to 0.91 for emotional neglect, and 0.61 to 0.78 for physical neglect [37]. Nakhaee and Garrusi [38] performed the Persian language validation and reliability studies for the test.…”
Section: Methodsmentioning
confidence: 99%
“…These forms of trauma have a lasting intensity and influence on the patient [46]. Moreover, according to a recent study has reported that ADHD cases were more commonly exposed to emotional abuse and neglect and had PTSD symptoms frequently [47]. These results may be interpreted as PTSD is one of the sequelae of early childhood maltreatment and exposure to early life trauma is a risk factor for adult PTSD.…”
Section: Discussionmentioning
confidence: 99%